Agroecology in the educational context of Ceará: adding popular knowledge to education - Paiva, Francisca Pereira; Aguiar, Maria Ivanilda de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2023)
The objective of this article is to promote academic debate about Agroecology in the educational context of Ceará. It aims to foment reflection on environmental education practices in the educational context of Ceará as an intrinsic aspect of agroecology. The methodology used was a systematic literature review built based on bibliographic data; the study presents itself as an encounter contextualized to the theme. built based on bibliographic data, the study appears as a meeting contextualized the theme. Articles registered in the Google Scholar database were used to identify the existence of research on agroecology in the school context, as well as data on consolidated experience of preparation and knowledge from projects undertaken. The analysis of the academic productions found revealed an insignificant amount of work on agroecology in schools in Ceará of 0.30%, showing that this dimension of agroecology in the practice of the school environment is being given little attention in academic activities and curricula. With this, the work presents a discussion on the topic, in order to drive the developments in the academic environment and the construction of a thought to attribute greater appreciation to knowledge as a factor for human, economic, social development and environmental protection.